2011
DOI: 10.1007/s00296-010-1563-6
|View full text |Cite
|
Sign up to set email alerts
|

The ossification diathesis in the Medici family: DISH and other features

Abstract: The Medici family ruled Florence for most of the period from the 1430s to the 1730s, with the senior (primogenito) branch predominating until the line ended in the 1530s and the cadet (secondogenito) branch predominating thereafter. Recent studies have identified a familial syndrome consisting of cutaneous symptoms, peripheral arthropathy and spinal ankylosis in the primogenito branch of the family, and the presence of diffuse idiopathic skeletal hyperostosis (DISH) in two members of the secondogenito branch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…A recent study of adult males in the senior branch of the family found evidence of a 'Medici syndrome,' consisting of a psoriatic-DISH arthropathy, extending across five generations [33,34]. Although Cosimo I was born into the cadet branch of the family and was only distantly related to the senior branch through his paternal ancestors, his mother was a member of the senior Medici line.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study of adult males in the senior branch of the family found evidence of a 'Medici syndrome,' consisting of a psoriatic-DISH arthropathy, extending across five generations [33,34]. Although Cosimo I was born into the cadet branch of the family and was only distantly related to the senior branch through his paternal ancestors, his mother was a member of the senior Medici line.…”
Section: Resultsmentioning
confidence: 97%
“…Penelitian ini merujuk pada penelitian keluarga Medici di wilayah Eropa. Keluarga Medici memerintah Florance pada tahun 1430-an hingga 1730-an (Weisz, Matucci-Cerinic, Lippi, & Albury, 2011). Padgett dan asistennya mengumpulkan data untuk melihat jaringan sosial keluarga kaya ini melalui hubungan partinial, pernikahan, lingkungan, kekayaan pribadi, jabatan politik, kenggotaan kelas sosial (Padgett & McLean, 2011).…”
Section: A Pendahuluanunclassified
“…The evidence suggests a complex hereditary condition that affected both the senior line of the family and also the cadet line from which Cosimo was descended. 4,6,7 Cosimo was reported to have suffered from disabling joint problems throughout his middle and later years, and further information was gained about these problems when his pathology was recently investigated in the exhumed skeleton. X-rays showed no evidence of gout, which was the premodern explanation of Medici joint pathologies, but they identified a number of arthritic and other pathological changes in the spine and leg bones.…”
Section: Portrait 1: Cosimo I De' Medici In Armourmentioning
confidence: 99%